Pre- hispanic epistemologies of Latin America and psycho-social change: the case of the concepts of communication rights and media development: El caso de los conceptos derecho a la comunicación y desarrollo mediático - Vieira Ouriques, Evandro (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The article draws attention to the urgency of including pre-hispanic epistemologies in Latin American communication thought. The autor considers the evidence of the non-dualistic nature of this knowledge to potentiate the psycho-social change, decisive to construct more symmetry in south-north relations and the consequent sustainability and democracy. As a particular case, the paper applies the non-dualistic epistemology to analyze the concepts communication rights and media development, from the psycho-political perspective of the concept mental territory ( created by the autor in the field of his psycho-political economy of communication and culture), taking into account the urgency to interlink the concept development with the concept of sustainable.